Gut microbiome and short-chain fatty acids associated with the efficacy of growth hormone treatment in children with short stature - He, Pingsihua; Lyu, Yongfen; Shen, Xinyuan; Liu, Wenxin; Zhang, Ying; Li, Yan; Huang, Yuying; Xu, Liya; Zhang, Liang; Guo, Sheng (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate associations between fecal microbiota, short-chain fatty acids (SCFAs), and the efficacy of recombinant human growth hormone (rhGH) treatment in children with growth hormone deficiency (GHD) or idiopathic short stature (ISS).MethodsA 2-phase cohort study was conducted. Phase I included 102 participants (GHD: n = 33, ISS: n = 28, controls: n = 41) for cross-sectional analysis using 16S rRNA sequencing and targeted metabolomics to compare microbial diversity, predicted metabolic pathways, and SCFA levels. Phase II longitudinally monitored 61 rhGH-treated children (GHD = 33, ISS = 28) over 2 years, assessing growth velocity, IGF-1 levels, and fecal microbiota/SCFA dynamics. Statistical analyses included alpha/beta diversity metrics, LEfSe, PERMANOVA, and redundancy analysis (RDA) to link microbial/SCFA profiles with clinical outcomes.Results(1). Microbiota Dysbiosis: Untreated GHD/ISS children exhibited reduced beneficial taxa (e.g., Faecalibacterium, Akkermansia) and increased pathobionts (e.g., Streptococcus, Collinsella) compared to controls (PERMANOVA: R2 = 0.114, P = 0.001). (2). Metabolic Pathways: GHD/ISS groups showed enrichment in xenobiotic degradation (e.g., atrazine) and deficits in nutrient-associated pathways (e.g., carotenoid biosynthesis). (3). rhGH Effects: Treatment increased beneficial taxa (e.g., Bifidobacterium, Faecalibacterium) and modulated amino acid/lipid metabolism pathways (e.g., glycine-serine-threonine metabolism, P = 0.035). (4). SCFAs and Growth Velocity: Higher growth velocity percentiles correlated with elevated acetic acid (GHD-treated: 1952 ± 962.4 vs. untreated: 1290 ± 886.0 μg/g, P = 0.037) and butyric acid levels.ConclusionGHD, ISS, and healthy children have different fecal microbiota compositions and SCFA metabolisms. rhGH therapy partially restores microbial balance and alters metabolic pathways, with SCFA levels associated with treatment efficacy. These findings highlight the gut microbiome as a potential modulator of rhGH response and provide insight into microbiota-targeted therapies to improve growth outcomes (e.g., “probiotic interventions”).